PENGARUH SERVICE QUALITY, BRAND IMAGE, DAN BRAND TRUST TERHADAP KEPUTUSAN PENGGUNAAN MASKAPAI CITILINK DI INDONESIA - Deza , Saffana Khalisha; Agus, Agus Maolana Hidayat (FEB Universitas Sam Ratulangi Manado, 2024)
Aviation companies are a service industry that drives the national economy through air transportation services. This industry is the third most affected by Covid-19 in the transportation sector. The decline in demand, travel restrictions, and state regulations have changed passengers' perceptions or perspectives regarding air transportation through service quality, brand image, brand trust, and usage decisions of airline passengers. This research aims to determine the response and influence of changes in passenger perceptions or perspectives regarding air transportation through service quality, brand image and brand trust on the decision to use Citilink airline in Indonesia after the Covid-19 pandemic. This type of research is quantitative with a descriptive approach involving 420 airplane passengers who used Citilink in Indonesia after the pandemic. The sampling technique in this research uses non-probability sampling, which is processed using SmartPLS 3.2.9 This research proves that service quality, brand image and brand trust have a positive and significant influence at various levels on the decision to use Citilink airline in Indonesia with consumer perceptions which can be categorized as good.